The cointegration and causality tests for tourism and trade in Malaysia - Kadir, Norsiah; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2010)
This paper examines the relationship between tourism and trade that might have evolved in the development of Malaysian economy by using cointegration and causality tests. All analyses have been conducted with quarterly data of international tourism receipts, exports, imports and total trade of Malaysia, over the period of 1995:1 through 2006:4. The results of the unit root tests indicate that the data are stationary in first-difference and not in level. The results of the JJ co integration test however, show that all the series are not cointegrated in the long run, hence, long-run equilibrium did not exist between all the series. Using Granger-causality tests the study found that there is one-way causal effect (unidirectional causality) running from exports to international tourism receipts at 5% significance level. The causality test also shows a one-way causal effect running from imports to international tourist receipts at 5% significance level and total trade to international tourism receipts at 10% significance level. This leads to a conclusion that increase in total trade, exports and imports will cause growth in the tourism sector, which means that most of tourist arrivals are related to business tourism. Therefore, to increase and sustain in the growth of tourism sector, future economic policy should focus more on tourism and trade related, in order to generate more foreign exchange earning to Malaysia